Dimensional Distribution of Anxiety and Depression in College Students in a Rural Setting: Relationship with Stress, Well-being, and Quality of Life - Nilamadhab Kar; Mithila Das; Brajaballav Kar; Namita Rath; Shreyan Kar (Indian Journal of Social Psychiatry)
Background: Information about the anxiety and depression of students in rural areas of India is scant. We evaluated stress, coping strategies, quality of life (QOL), and well-being of students along with the dimensional and categorical distribution of anxiety and depression in a cross-sectional study in a rural college. Materials and Methods: It was an online questionnaire-based survey using the Patient Health Questionnaire-9 for depression, general anxiety disorder-7 for anxiety, and the WHO-5 Well-Being scale for well-being. Stress in the previous month, nature of stress, coping strategies, and QOL on a scale of 1 (worst) to 10 (best) were also assessed. Results: The dimensional distribution of anxiety and depression suggested the pervasiveness of these problems among students. Categorically, a considerable proportion of students had clinical levels of anxiety (32.2%), depression (40.3%); and 24.8% of students had both of them. Stress in the past month was reported by 34.2% of students, which was linked significantly with the severity of anxiety and depression. Common stressor were financial problems, family-, career-, and job-related issues. Stress, anxiety, and depression were negatively correlated with well-being and QOL. Many coping strategies were reported; more than half of the students found helping others, creative hobbies, hoping for the best, music, talking to others, yoga and exercises, prayer, and religious activities helpful. Conclusions: The results highlight the pervasive presence of anxiety and depression in college students, which are linked to stress, and have an impact on their well-being and QOL. These require specific attention for management.